Pengaruh Persepsi Kualitas Produk, Citra Merek dan Word of Mouth Terhadap Keputusan Pembelian Produk Perawatan Skintific - Kiki Restu Handayani; Retno Susanti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The purpose of this study was to analyze the effect of perceived product quality, brand image and word of mouth on purchasing decisions for Skintific care products. The population in this study were consumers who had purchased Skintific products with a sample of 130 people with the sampling technique used was purposive sampling. The data collection method used a questionnaire. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and determination coefficient test. The results of the analysis state that perceived product quality, brand image and word of mouth have a positive effect on purchasing decisions for Skintific care products through Shopee e-commerce in Surakarta. Hypothesis testing obtained that perceived product quality has a significant effect on purchasing decisions for Skintific care products through Shopee e-commerce in Surakarta. Brand image has a significant effect on purchasing decisions for Skintific care products through Shopee e-commerce in Surakarta. Word of mouth has an insignificant effect on purchasing decisions for Skintific care products through Shopee e-commerce in Surakarta. The F test states that the research model of the influence of the independent variable on the dependent variable is correct. The coefficient of determination test shows that perceived product quality, brand image and word of mouth are able to explain purchasing decisions by 43.2%.